Risk Factors of Pneumonia in Patients with COVID-19 at Bang Pa-in Hospital, Phra Nakhon Si Ayutthaya province - Jittanoon, Thapakorn (Journal of Preventive Medicine Association of Thailand, 2023)
Objective: To study the factors resulting in the incidence of pneumonia in COVID-19 patients who were treated at Bang Pa-in Hospital, Phra Nakhon Si Ayutthaya province. Methods: This was an analytical retrospective study in which data were collected from medical records of 598 COVID-19 patients admitted at Bang Pa-in Hospital in Ayutthaya province from 1 January 2021 to 31 December 2021. Descriptive data were expressed as frequency and percentage. The factors resulting in the incidence of pneumonia were analyzed by using simple and multiple regression analysis. Results: 175 out of 598 COVID-19 patients were diagnosed as pneumonia, 64.57% were female, and 54.29% were below 60 years of age. Moreover, 46.86% had hypertension as an underlying condition, non-smokers were 94.03%, and the main clinical symptom observed was cough in 73.71%. When analyzing the risk factors for the progression of pneumonia in COVID-19 patients without laboratory results, age ≥ 60 years (adj. OR 2.36, 95%CI 1.38-4.03), hypertension (adj. OR 3.25, 95%CI 1.64-6.47), fever ≥ 37.5°C (adj. OR 2.74, 95%CI 1.47-5.09) and respiratory rate ≥ 20 breaths per minute (adj. OR 6.24, 95%CI 2.97-13.13) were significantly associated. Including laboratory findings to the analysis, hypertension (adj. OR 3.17, 95%CI 1.07-9.36), fever ≥ 37.5°C (adj. OR 3.26, 95%CI 1.27-8.39, respiratory rate ≥ 20 breaths per minute (adj. OR 9.57, 95%CI 2.98-30.72) and abnormal levels of C-reactive protein (CRP) (adj. OR 2.16, 95%CI 1.04-4.49) were significantly associated with pneumonia in the study. Conclusion: This study revealed that age ≥ 60 years, hypertension, fever ≥ 37.5°C, respiratory rate ≥ 20 breaths per minute and abnormal levels of C-reactive protein (CRP) were significantly associated with pneumonia in COVID-19 patients. These findings could be valuable for the surveillance, prevention, and treatment of pneumonia in COVID-19 patients.